Methodological apparatus and instruments for personalization in adaptive tutoring systems - Niesler, Gracja; Niesler, Andrzej (Adaptacyjny system wspomagania nauczania: aparat metodologiczny oraz narzędzia personalizacji, 2019)
Most learning difficulties are rooted in the individual learner’s perspective. As a common practice, modern educational systems are formed on the basis of a set of standardized didactic methods, which are then used repeatedly in the teaching of the whole population. However, every learning group consists of individuals with different cognitive model and individual learning process. The key to provide effective knowledge absorption is to adapt the set of teaching methods and use it in such a way that the individual characteristics of the learner are taken into account to the highest, reasonable extent. This paper addresses the problem of defining the personalization and adaptability of the learning process in the context of tutoring systems. The authors propose a methodological apparatus for identifying and acquiring the user’s individual characteristics and transforming it into a set of tools and instruments that can provide adaptability in tutoring systems
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 60-73
Keywords: informatyka ekonomiczna